PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP DEVIDEN SECARA INTERNAL PADA PERUSAHAAN INDUSTRI PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Kiki Fitriani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the Effect Of Internally Profitability, Leverage, and Liquidity On Dividends In Plastic and Packaging Industry Companies Listed On The Indonesian. The ratio used to measure dividend is the net profit margin, return on investment, return on equity, debt to asset ratio, debt to equity ratio, current ratio, dividend payout ratio. The method used to observe the Effect Of Internally Profitability, Leverage, and Liquidity On Dividends is to use simple linear regression.    The data used in this study are secondary data, namely financial statements and annual reports. The data recorded on the Indonesia Stock Exchange (IDX) for 5 years from the period 2012 to 2016. Sampling was done by purposive sampling, which used simple linear regression analysis, t test and f test. Data analysis uses several linear regression analysis with SPSS 25.      The results of the analysis show that profitability, leverage, liquidity have a significant effect on the dividend of plastic and packaging industry companies listed on the Indonesia Stock Exchange.  Keywords: Profitability, Leverage, Liquidity, Dividends